Peer Approach in Improving Handwashing Behavior Using Soap in Elementary Students - Pau Djaka, Yanty Ariani; Romeo, Petrus; Ndun, Helga J. N. (Universitas Nusa Cendana, 2023)
The behavior of washing hands with soap must be instilled early in school-age children, considering that children are generally more prone to disease. Children from an early age will be more likely to adopt clean and healthy behavior, including washing hands, as they are sensitive to stimuli; therefore, children will be easy to guide and direct. The behavior of handwashing with soap can be introduced through a peer approach. The study aimed to analyze the effect of the peer approach in improving the behavior of washing hands with soap students at SD Negeri Tenau Kupang. The method used in this research was a pre-experimental research design with one group pretest-posttest design. The sample consisted of 39 students from class V. The results showed a mean difference in the knowledge with 80.65 before treatment (pre-test) and 95.81 at post-test. Handwashing behavior also differed from before and after treatment for 22.59% and 64.51%, respectively. The school can use the method to educate and train elementary school children to practice handwashing with soap.